CONTRIBUTIONS OF VYGOTSKY’S HISTORICAL-CULTURAL THEORY TO SPECIAL AND INCLUSIVE EDUCATION: AN ANALYSIS DIRECTED TO CHILDREN WITH AUTISTIC SPECTRUM DISORDER - Benvindo de Souza, Cirlene; Antonia da Silva, Ivone (Revista Gênero e Interdisciplinaridade, 2024)
This article examines how Lev Vygotsky’s historical-cultural theory can be applied to the education of children with Autism Spectrum Disorder (ASD). With an emphasis on concepts such as the Zone of Proximal Development (ZPD), mediated learning, social interaction, adaptation of teaching material and a focus on children’s abilities and individuality, the study proposes methodological adaptations that can significantly benefit the inclusion and educational development of these children. students